2010
DOI: 10.1073/pnas.1003904107
|View full text |Cite
|
Sign up to set email alerts
|

No evidence of nanodiamonds in Younger–Dryas sediments to support an impact event

Abstract: The causes of the late Pleistocene megafaunal extinctions in North America, disappearance of Clovis paleoindian lithic technology, and abrupt Younger-Dryas (YD) climate reversal of the last deglacial warming in the Northern Hemisphere remain an enigma. A controversial hypothesis proposes that one or more cometary airbursts/ impacts barraged North America ≈12,900 cal yr B.P. and caused these events. Most evidence supporting this hypothesis has been discredited except for reports of nanodiamonds (including the r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
77
2
1

Year Published

2012
2012
2016
2016

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 50 publications
(83 citation statements)
references
References 34 publications
3
77
2
1
Order By: Relevance
“…Daulton et al (2010) found no YDB NDs and concluded that their findings cast doubt on the presence of YDB NDs, although they pointed out that YDB NDs might "occur inhomogeneously and only in some of the YD-boundary carbons and hence are not observed in our study" (p. 16046). Daulton et al (2010) also noted that other minerals, including nanocrystalline copper and copper oxide, could be misidentified as several of the proposed diamond polytypes, because of crystallographic similarities between copper and diamond.…”
Section: Introductionmentioning
confidence: 79%
See 3 more Smart Citations
“…Daulton et al (2010) found no YDB NDs and concluded that their findings cast doubt on the presence of YDB NDs, although they pointed out that YDB NDs might "occur inhomogeneously and only in some of the YD-boundary carbons and hence are not observed in our study" (p. 16046). Daulton et al (2010) also noted that other minerals, including nanocrystalline copper and copper oxide, could be misidentified as several of the proposed diamond polytypes, because of crystallographic similarities between copper and diamond.…”
Section: Introductionmentioning
confidence: 79%
“…Israde-Alcá ntara et al (2012b) used multiple analytical techniques to demonstrate that the YDB NDs from Lake Cuitzeo, Mexico, are cubic NDs, n-diamonds, i-carbon, and lonsdaleite-like crystals. Israde-Alcá ntara et al (2012b) also identified several problems and limitations of the study by Daulton et al (2010), who reported an absence of YDB NDs in carbon spherules at Murray Springs and Arlington Canyon. First, Daulton et al (2010) searched for and failed to find NDs within carbon spherules at Murray Springs, but neither Firestone et al (2007) nor Kennett et al (2009a) reported finding carbon spherules at that site, making the related absence of NDs unsurprising.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Other investigators have pointed out the possibility of a combination of human-caused and climate-related causes of extinction (see discussion in Barnosky et al, 2004). Although all three mechanisms are controversial, the extraterrestrial impact hypothesis has received a significant amount of criticism (e.g., Daulton et al, 2010;Pinter et al, 1998Pinter et al, , 2011Holliday et al, 2014;Meltzer et al, 2014) and is not considered further here. No attempt is made to discuss the pros and cons of the human vs. climate change causes for megafaunal extinction in North America, but some of the findings presented here have relevance to the debate on these two causes for mammoth extinction specifically on the Channel Islands.…”
Section: Implications For Causes Of Mammoth Extinctionmentioning
confidence: 99%